Perbedaan kinerja keuangan antara bank pemerintah dengan bank swasta nasional yang terdaftar di bursa efek indonesia tahun 2015 - 2019 - Willem, Willem; Binti, Margo Tando; Dinan, Dinan; Hartini, Sri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the difference in financial performance between state-owned banks and national private banks listed on the Indonesia Stock Exchange (IDX) in 2017 – 2019. The financial performance variables studied consisted of Capital Adequacy Ratio (CAR), Net Profit Margin (NPM). and Return On Assets (ROA). The population of this study were all banks listed on the Indonesia Stock Exchange (IDX) in 2015–2019. Of all banks listed on the Indonesia Stock Exchange (IDX) in 2015–2019, 29 banks met the criteria as samples in this study, which consists of 5 state-owned banks and 24 privately-owned banks. The research hypothesis was tested by using the analysis technique of the T-Test and Mann-Whitney Test. The results showed that from the aspect of the Capital Adequacy Ratio (CAR) it was not proven that there was a significant difference in performance between state-owned banks and private banks. Judging from the aspect of Net Profit Margin (NPM) and Return On Assets (ROA), it is proven that there is a significant difference in performance between state banks and private banks. Based on the results of this study, it is recommended that investors or potential investors always consider aspects of Net Profit Margin (NPM) and Return On Assets (ROA) in making investment decisions, while the Capital Adequacy Ratio (CAR) factor can be ignored.